Adaptability of Biofilm Formation in Streptococcus Pneumoniae to Various Growth Conditions - Zainab Rashid Hameed; Anfal Shakir Motib; Adawia F. Abbas (Institute of Medico-legal Publications Pvt Ltd, 2021)
Streptococcus pneumoniae is one of the major general causes of important diseases world-wide such aspneumonia and meningitis with a high morbidity and mortality in adults especially in elderly people.Pneumococcal biofilms are essential for colonization and persistence, and it is important to continue toinvestigate the environmental conditions which affect their formation. This study came to find out theadaptability of biofilm formation in S. pneumoniae that causes pneumonia in Diyala city and diagnose themwith PCR method by using 16SrRNA for pneumococcal detection in addition to the roads bacteriologyculture test. In this study, 192 sputum samples were collected from Bacteriology Unit of Baquba teachinghospital, Chest Diseases Consultation Clinic and Al-Khalis General Hospital. It appeared that 122 (64%)samples showed no growth while 70 (36%) showed positive growth. Streptococcus pneumoniae isolateswere obtained from 32 isolates. The results of this study showed amplify 1500 bp domain of 16SrRNA byPCR, which was positive in 32 (100%). In addition, the PCR product of the samples were sent for sequencingto identify the Streptococcus pneumoniae strains. The results appeared that the strains of S. pneumoniae thatcause pneumonia in Iraq especially in Diyala city are K10 and D39 strains. Biofilm formation assay wasmeasured by using microtiter plate in three different media and the membrane formation was measured atfour times of bacterial growth phases to show the adaptability of biofilm formation in different environmentalconditions in different media culture. Data of the current study showed that the ability of pneumococcal toform biofilm was better when using a poor medium such as nutrient broth, and the highest value was at thestationary phase.